Kebijakan Hukum Perlindungan Pengetahuan Tradisional (Traditional Knowledge) di Afrika Selatan - Rahmih Yunisyah Mawaddah (Universitas Islam Indonesia, 2022)
Traditional knowledge is a collection of knowledge, skills and practices developed within an indigenous community group, thus forming a separate identity, and being passed on from one generation to the next. This traditional knowledge is known and transmitted orally so it is difficult to prove in the future. Therefore it requires protection that can provide benefits to indigenous peoples who have this inheritance. This study aims to determine whether policies regarding traditional knowledge in South Africa are in accordance with various applicable international laws. This research is a normative literature study. The results of this study are that traditional knowledge remains extremely difficult to impart because the knowledge produced is difficult to prove simply because it is passed down orally, besides that the rules that are enforced are still limited even though he Nagoya Protocol has been ratified as well as rules regarding natural resources, biological or genetic resources as well as traditional knowledge, namely the National Environment Management Biodiversity Act 2004 has been enacted and amended by the National Environmental Management through Law No. 14 of 2013, in addition to the Amendment of Patents Law 2005 as well as the Intellectual Property Law No. 28 of 2013 to protect existing traditional knowledge in the country. One of the foresaid knowledge is the use of hoodia plant as an anti-obesity drug.Keywords: Policy, Hoodia, Traditional Knowledge AbstrakPengetahuan tradisional (traditional knowledge) merupakan sekumpulan pengetahuan, keterampilan dan praktik yang dikembangan dalam suatu kelompok masyarakat adat, sehingga membentuk sebuah identitas tersendiri, dan diwariskan dari satu generasi ke generasi. Pengetahuan tradisional ini dikenal dan disebarkan secara lisan sehingga sulit dibuktikan dikemudian hari. Oleh karena itu memerlukan perlindungan yang dapat memberikan manfaat kepada masyarakat adat yang mempunyai warisan tersebut. Penelitian ini bertujuan untuk mengetahui kebijakan mengenai pengetahuan tradisional di Afrika Selatan apakah telah sesuai dengan berbagai hukum internasional yang berlaku. Penelitian ini merupakan normatif studi literatur. Hasil dari penelitian ini bahwa pengetahuan tradisional masih sangat sulit untuk diberikan dikarenakan pengetahuan yang dihasilkan sulit dibuktikan hanya karena diwariskan secara lisan, selain itu aturan yang diberlakukan belum meluas masih terbatas walaupun telah meratifikasi Nagoya Protocol dan juga membuat dan mengamandemen aturan yang telah ada mengenai sumber daya hayati atau sumber daya genetik juga pengetahuan tradisional yakni National Environment Management Biodiversity Act 2004 yang diamandemen dengan National Environmental Management Laws Amendment Act 14 of 2013, selain itu Amendment Patents Act 2005 dan juga Intellectual Property Laws Amendment Act 28 of 2013 untuk melindungi pengetahuan tradisional yang ada di negara tersebut. Salah satunya tumbuhan hoodia yang dapat dijadikan sebagai obat antiobesitas.Kata-kata Kunci: Kebijakan, Hoodia, Pengetahuan Tradisional